DETERMINATION OF GENDER PERCEPTIONS OF YOUTH AND AFFECTİNG FACTORS - ORHAN, İlksen and DOĞAN YÜKSEKOL, Özlem (Göbeklitepe Medical Science Journal, 2022)
The aim of this research is to determine the gender perceptions of young people and the affecting factors. This study has been carried out to total of 309 young people between the ages of 10-24 living in a city center in eastern Turkey. The data were collected using the ‘Descriptive İnformation Form’ and ‘Gender Perception Scale’. Evaluated data in SPSS package program; percentage, Standard deviation, frequency, mean minimum-maximum values were analyzed using Chi square, Mann Whitney-U, Kruskall Wallis tests. The mean gender perception score of the youth was 85.94±11.10, and it was found that women’s gender perceptions were more positive than men. There was no statistically significant difference between gender, family type, place of residence, number of siblings, family income level, education level of parents and presence of partners and gender perception of the youth participating in there search (p>0.05). In the study, it was determined that the gender perception of young people with a relationship period of more than one year was more positive (p<0.005).